Pengobatan Gratis Pasca Banjir Sebagai Upaya Pencegahan Penyakit dan Peningkatan Kesehatan Masyarakat Terdampak - Novrina Situmorang; Alexander P. Marpaung; Maestro B. U. Simanjuntak; Ivonne R. V. O. Situmeang; Paul S. M. L. Tobing; Inda M. H. Sinaga; Julenda Sebayang; Sanggam B. Hutagalung; Doharjo Manullang; Harry Butar-butar; Adrian Khu; Wijaya Taufik Tiji; Eka Samuel P. Hutasoit; Irene R. T. Damanik; Menang Bastanta Tarigan; Jerry Tobing; Riana Pangaribuan; Lylys Surjani; Evirosa Simanjuntak; Salomo G. U. Simanjuntak; Suryati Sinurat; Surjadi Rimbun; Budi Dermanta Sembiring; Nasib M. Situmorang; Hanjaya Hanjaya (Universitas Methodist Indonesia, 2025)
Flood disasters often cause various health problems such as skin diseases, diarrhea, acute respiratory infections, and leptospirosis due to environmental contamination and limited access to health services. This community service activity aimed to provide free medical treatment for flood-affected communities as an effort to prevent disease transmission and improve public health status. The activity was carried out through health examinations, medication distribution, health education, and environmental sanitation counseling. The target participants were residents affected by flooding in the designated area. The results showed that most patients experienced skin infections, diarrhea, fever, and respiratory tract infections. Health education increased community awareness regarding clean and healthy living behavior after floods. Free medical services were proven to be effective in reducing complaints and preventing more serious complications among the affected population.